2019
DOI: 10.1155/2019/7463815
|View full text |Cite
|
Sign up to set email alerts
|

To Evaluate the Effect of Chronic Obstructive Pulmonary Disease on Retinal and Choroidal Thicknesses Measured by Optical Coherence Tomography

Abstract: Purpose To evaluate the retinal and choroidal thicknesses in patients with chronic obstructive pulmonary disease using optical coherence tomography. Methods The study included 26 patients with chronic obstructive pulmonary disease (COPD) and 26 age-matched healthy control groups. Detailed ocular examinations were performed on all participants. Cirrus EDI-OCT (enhanced depth imaging-optical coherence tomography) was used for choroidal thickness measurements with frame enhancement software. The subfoveal area wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…have found no significant difference between the COPD patients and the control group in terms of CMT. [ 3 9 ] The CMT values obtained in the current work are attributed to the active autoregulatory mechanisms in the retinal circulation. [ 14 ] In addition, compared with choroidal circulation the retinal circulation is more sensitive to blood PaO 2 levels and responds to changes in blood oxygen levels more rapidly and actively to protect the central retinal functions.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…have found no significant difference between the COPD patients and the control group in terms of CMT. [ 3 9 ] The CMT values obtained in the current work are attributed to the active autoregulatory mechanisms in the retinal circulation. [ 14 ] In addition, compared with choroidal circulation the retinal circulation is more sensitive to blood PaO 2 levels and responds to changes in blood oxygen levels more rapidly and actively to protect the central retinal functions.…”
Section: Discussionmentioning
confidence: 74%
“…[ 10 ] Similarly, Alim et al . [ 3 ] reported that the severe COPD patients demonstrated significantly reduced SCFT compared with the healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corroboratory genetic evidence for this was also observed, with genetic predisposition to lower FEV1 and FVC being associated with thinner RNFL and PS layers. Thinning of the RNFL and choroid have been associated with COPD in a number of cross-sectional studies (81)(82)(83)(84)(85). OCT studies in the context of infectious pneumonia are few in number and mostly relate to SARS-CoV-2 (COVID-19), which is variably reported to be associated with reduced macular thickness and RNFL thinning (86), as well as increased RNFL and GCC thickness compared to controls (87).…”
Section: Discussionmentioning
confidence: 99%
“…Choroidal thinning in patients with COPD is due to decreased choroidal blood flow and decreased ocular perfusion pressure [24]. The chronic inflammation and hypoxia in subjects with COPD may lead to an increase in the diameter of the retinal veins, impaired hemodynamics, lower retinal arterial oxygen saturation causing thinning of the retinal nerve fiber layer, and subfoveal choroidal thickness [25,26].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%